Impact of the established healthy canteens and restaurants in Shanghai on usage of oil， salt， and sugar， and on nutritional knowledge and behavior of diners - MAI Shupeng; SONG Qi; SHI Zehuan; QU Mengying; SHEN Liping; LU Wei; SUN Zhuo; WANG Zhengyuan; ZANG Jiajie (Shanghai yufang yixue, 2023)
ObjectiveTo evaluate the changes of the usage of oil， salt， sugar and nutritional knowledge and behavior intervention among diners before and after the establishment of healthy canteens and restaurants in Shanghai.MethodsA comprehensive intervention was conducted through the establishment of healthy canteens and restaurants， encompassing interventions such as oil， salt， and sugar management， improvement of nutritional environment， staffing and training activities， and nutrition labeling guidance. A pre-post self-controlled study design was used to compare changes in oil， salt and sugar usage， as well as diners’ knowledge and behaviors related to nutrition and nutrition labeling， before and after the intervention.ResultsAfter intervention， the total usage of oil， salt， and sugar per meal in the canteens and restaurants decreased by 18.33%， 14.83%， and 13.66%， respectively，and all had statistically significance differences（P<0.001）. The awareness rate of "cooking oil intake"， "salt intake"， and "added sugar intake" among diners increased from 24.07% to 38.04%， 58.52% to 71.28%， and 26.85% to 45.01%， respectively. The awareness rate of "daily food types" and "weekly food types" increased from 43.07% to 56.53% and 49.52% to 64.32%， with significant differences （P<0.001）. The rate of understanding the content of nutrition labels increased from 66.91% to 76.90%， the awareness rate of nutrition labels increased from 53.59% to 69.06%， the rate of active reading of nutrition labels among diners increased from 73.38% to 81.23%， and the rate of selecting and purchasing food based on the information of nutrition labels increased from 69.27% to 77.79%， all of which were statistically significant （P<0.001）.ConclusionThe comprehensive interventions carried out through the creation of healthy canteens and restaurants have significantly impact on usage of oil， salt， and sugar， as well as on the nutritional knowledge and behaviors of diners.